1994
DOI: 10.1021/jm00034a018
|View full text |Cite
|
Sign up to set email alerts
|

Dibasic (Amidinoaryl)propanoic Acid Derivatives as Novel Blood Coagulation Factor Xa Inhibitors

Abstract: Since activated factor X (FXa) is a coagulant enzyme that generates thrombin and participates in both intrinsic and extrinsic coagulation pathways, inhibition of FXa may be more effective than inactivation of thrombin for interrupting blood coagulation. To assess the possible effectiveness of FXa inhibition as an anticoagulant, we designed and synthesized 3-(amidinoaryl)-2-[4-[(3S)-3-pyrrolidinyloxy]phenyl]propanoi c acid derivatives as low molecular weight, nonpeptidic, orally active FXa inhibitors. These der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
79
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(80 citation statements)
references
References 11 publications
1
79
0
Order By: Relevance
“…The structure of the DX-9065a-bound factor Xa was the first inhibitor complex structure published (13). DX-9065a was developed by Daiichi Pharmaceutical Co., Ltd., Tokyo, and inhibits factor Xa with K i ϭ 41 nM; IC 50 ϭ 92 nM at pH 8.4 (46,47) and K i ϭ 103 nM; IC 50 ϭ 208 nM at pH 7.4 (data not shown). Although the chemical structure and the binding mode of this inhibitor are different from those of FX-2212a (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The structure of the DX-9065a-bound factor Xa was the first inhibitor complex structure published (13). DX-9065a was developed by Daiichi Pharmaceutical Co., Ltd., Tokyo, and inhibits factor Xa with K i ϭ 41 nM; IC 50 ϭ 92 nM at pH 8.4 (46,47) and K i ϭ 103 nM; IC 50 ϭ 208 nM at pH 7.4 (data not shown). Although the chemical structure and the binding mode of this inhibitor are different from those of FX-2212a (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Edoxaban was first synthesized in Japan in 1994 in the Daiichi laboratories, 13 and the preclinical work was also done in Japan. 14 After the first-in-human, proof of concept, and dose-ranging work was completed, again much of it in Japan, 15 there were 3 observations that suggested edoxaban was worthy of further investigation: there were very few food and drug interactions; it was available in pill form that provided a stable level of an-Clinical Research and Therapeutics on a chip" is placed in a microfluid test chamber, which is then sealed and drugs can be infused as well as electrical currents delivered to stimulate the cells.…”
Section: Review Antman Emmentioning
confidence: 99%
“…DX-9065a, which is the progenitor of small-molecule fXa inhibitors, was found to possess an amidine moiety that binds the S1 pocket [1], and numerous structurally similar amidine derivatives were investigated as well [2]. Other studies of fXa inhibitors revealed that anthranilamide derivatives with a 4-methoxyphenyl group occupy the S1 binding pocket of fXa [3][4][5].…”
Section: Introductionmentioning
confidence: 99%